Cardiorenal Syndrome: Classification, Pathophysiology, Diagnosis, and Treatment Strategies. Issue 16 (16th April 2019) - Rangaswami, Janani; Bhalla, Vivek; Blair, John E.A.; Chang, Tara I.; Costa, Salvatore; Lentine, Krista L.; Lerma, Edgar V.; Mezue, Kenechukwu; Molitch, Mark; Mullens, Wilfried; Ronco, Claudio; Tang, W.H. Wilson; et al.
Abstract : Cardiorenal syndrome encompasses a spectrum of disorders involving both the heart and kidneys in which acute or chronic dysfunction in 1 organ may induce acute or chronic dysfunction in the other organ. It represents the confluence of heart-kidney interactions across several interfaces. These include the hemodynamic cross-talk between the failing heart and the response of the kidneys and vice versa, as well as alterations in neurohormonal markers and inflammatory molecular signatures characteristic of its clinical phenotypes. The mission of this scientific statement is to describe the epidemiology and pathogenesis of cardiorenal syndrome in the context of the continuously evolving nature of its clinicopathological description over the past decade. It also describes diagnostic and therapeutic strategies applicable to cardiorenal syndrome, summarizes cardiac-kidney interactions in special populations such as patients with diabetes mellitus and kidney transplant recipients, and emphasizes the role of palliative care in patients with cardiorenal syndrome. Finally, it outlines the need for a cardiorenal education track that will guide future cardiorenal trials and integrate the clinical and research needs of this important field in the future. Abstract : Supplemental Digital Content is available in the text.